Prostate-specific antigen dynamics predict individual responses to intermittent androgen deprivation - Renee Brady-Nicholls (Nature Portfolio, 2020)
Prostate specific antigen (PSA) is a biomarker for prostate cancer. Here, the authors develop a mathematical model where longitudinal changes in PSA levels predict responses to intermittent androgen deprivation in patients with prostate cancer.